Brazilian 'Travesti' Migrations Gender, Sexualities and Embodiment Experiences - Vartabedian, Julieta (Genders and Sexualities in the Social Sciences, 2018)
'Brazilian 'Travesti' Migrations offers a rich and nuanced analysis of the cultures of travestis in Rio de Janeiro and Barcelona. Emerging from a feminist ethics and paying particular attention to embodiment and aesthetics, it tells a moving and often heroic story of gender diverse lives, loves and bodies. This is a wonderful addition to sexuality and gender research.' -Sally Hines, Associate Professor of Sociology and Gender Studies, University of Leeds, UK. 'Vartabedian's fascinating ethnographic account reveals not only how some performances of femininity are valued more than others, but how these performances are simultaneously a way of enacting exoticized versions of Brazilianness. Importantly, she showcases the limitations of eurocentric sex/gender taxonomies for accommodating travesti ways of being and suggests that transgender studies further work to do if it is to interpret travesti lives without doing epistemological violence to them.' -Susan Stryker, Associate Professor of Gender and Women's Studies, University of Arizona, USA, and co-editor, TSQ: Transgender Studies Quarterly This book analyses the embodied and spatial experiences of Brazilian travesti sex workers who cross both, gender and (trans)national borders. Based on a multi-sited ethnography, it explores travestis' bodily transformations, their involvement in sex work, and the transnational migrations to Europe that many make. This engaging account combines rich ethnographic research with incisive analysis that draws on feminist and trans studies, queer theory (and its critiques), social and queer geography research, sex work and trans migration studies. It will appeal to students and scholars of migration, gender, sexuality and transgender issues. Julieta Vartabedian is a researcher at the Department of Sociology at the University of Cambridge, UK. In her work she combines gender studies, feminist theory, ethnographic and embodiment research. Her articles have been published in Qualitative Research and Sexualities.